INCOMPETENCE IN MANAGEMENT - Kasim S. Biktyakov (Plekhanov Russian University of Economics, 2017)
The article provides examples of erroneous decisions made by company executives. The most effective and illustrative method deals even with successful companies. Some companies are able to cope with the crisis, which was a result of hasty steps, others are not and they are ruined. The author instructs what should be done by the manager in order to avoid such situations and what should be omitted and how to minimize losses caused by incompetence in management. The article systematizes erroneous decisions and then moves them to practice. The main idea - lessons should be learned from mistakes.